Magnetism: Insights from the Thomas Young Experiment - Khumalo, Bhekuzulu (JOURNAL OF ADVANCES IN PHYSICS, 2021)
The principles of Thomas Young’s double slit experiment are used to find out further the nature of magnetism. This paper shows that not only can magnetism be defined as a wave but it allows us to understand the nature of all waves and concept of polarization in quantum mechanics. A wave pattern results from the interactions. It is something else before it organizes into a wave formation. In all, because of the nature of magnetic phenomenon, it must be studied at close range with the double slit experiment. This gives an incredibly unique insight. All data is available at figshare.com to share.